Last stand on the ocean shore : an unofficial Minecrafter's adventure - Cheverton, Mark (Mystery of Herobrine, 2015)
Gameknight999 seeks the Book of Wisdom in a mysterious underwater lair in order to stop the dangerous Herobrine.